Study of Copper Recovery Using Emulsion Liquid Membrane under Taylor-Couette Column - Kusumastuti, Adhi; Astuti, Widi; Qudus, Nur (KnE Social Sciences, 2019)
High demand on batik fabric signiﬁcantly increased wastewater volume from batik home industries. Copper, being used as mordanting agent, available in the highest concentration in industrial textile wastewater. Emulsion liquid membrane (ELM) is promising selective method to recover solute. Taylor-Couette column (TCC) was proposedtoextractcopperinsteadofusingconventionalreactorthatdisturbsemulsion stability. Experiment was done by varying volume ratio of emulsion to feed phase, carrier and internal phase concentration. Extraction efﬁciency of>98% was obtained at volume ratio of emulsion to feed phase of 1:5, carrier concentration of 4 wt. %, and internal phase concentration of 0.1 M, respectively. Keywords: Taylor-Couette column, emulsion liquid membrane, recovery, copper